Three-Dimensional Evaluation of the Effects of Kinesio Taping on Postoperative Swelling and Pain after Surgically Assisted Rapid Palatal Expansion - Murat Ulu; Özgür Gözlüklü; Çiğdem Kaya; Nuri Ünal; Hüseyin Akçay (eJournal of Oral Maxillofacial Research, 2018)
Objectives: The purpose of the present study was to evaluate the effects of kinesio taping on pain and swelling after surgically assisted rapid palatal expansion.